2011
DOI: 10.1007/s00228-011-1183-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with adverse drug reactions in hospitalised children: international multicentre study

Abstract: To reduce the risk of ADRs in children, clinicians and pharmacists should aim to minimise polypharmacy and be aware of higher ADR risks associated with some drug groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
117
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(142 citation statements)
references
References 34 publications
(43 reference statements)
18
117
2
1
Order By: Relevance
“…Few studies found female preponderance while certain others, no such correlation. 1,3,6,13,14 In our study, however, there was male The commonest ADRs were local site reactions (Table 1) which is in concordance with previous studies. According to a study done in Shanghai 1 and a systematic review by Smyth et al large proportion of ADRs were local site reactions and mostly due to vaccines.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Few studies found female preponderance while certain others, no such correlation. 1,3,6,13,14 In our study, however, there was male The commonest ADRs were local site reactions (Table 1) which is in concordance with previous studies. According to a study done in Shanghai 1 and a systematic review by Smyth et al large proportion of ADRs were local site reactions and mostly due to vaccines.…”
Section: Discussionsupporting
confidence: 92%
“…1,3,6,12,18 Drug classes according to ATC classification are divided into high-risk drugs (analgesics, antiepileptics, antibacterials, immunosuppressants, antimycotics and corticosteroids for systemic use) and low-risk drugs (others). 13 In the present study, anti-infectives and antiepileptics were among the most common classes of drugs causing ADRs suggesting caution during prescription.…”
Section: Discussionmentioning
confidence: 58%
“…In a further 40 cases, the LCAT (0, 66,81,133) showed 'good' IRR (κ = 0.6), whereas Naranjo (1, 90, 185, 4) remained 'moderate'.…”
Section: Resultsmentioning
confidence: 92%
“…59,[80][81][82][83] ADRs in children may differ from those in adults owing to age-dependent physiological characteristics that affect the pharmacokinetics and pharmacodynamics of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…ADVISE was a prospective, multicentre, observational cohort study conducted on five paediatric general medical wards in Australia (AUS), Germany (GER), Hong Kong (HK), Malaysia ). Further details on the methodology of that study, cohort description and overall drug utilisation are described elsewhere [16][17][18].…”
Section: Methodsmentioning
confidence: 99%